The maze runner - Dashner, James (New York: Delacorte Press, 2009)
"Sixteen-year-old Thomas wakes up with no memory in the middle of a maze and realizes he must work with the community in which he finds himself if he is to escape."
Keywords: Amnesia -- Fiction; Cooperativeness -- Fiction; Labyrinths -- Fiction